Subject specialization in a liaison librarian program - CATALDO, Tara Tobin; TENNANT, Michele R; SHERWILL-NAVARRO, Pamela; JESANO, Rae (Journal of the Medical Library Association, 2006)
The information specialist in context (ISIC) or informationist, a new career path evolving in health sciences, integrates hybrid specialists with formal training in both information management and a particular subject discipline or other expert training into clinical or research teams [7, 8]. The college of nursing liaison is not a nurse but has employed a variety of strategies to gain the needed expertise to provide such integrated service, including her previous experience as a hospital librarian working closely with nurse educators, appropriate continuing education courses from MLA and nursing organizations, extensive reading in the discipline, and discussions with faculty about their areas of specialization and research interests.